#### Answer

-16

#### Work Step by Step

$3(4-7)+(-2)-5\ \longrightarrow$ resolve expression in parentheses
=$3(-3)+(-2)-5\ \longrightarrow$ multiply
=$-9+(-2)-5\ \longrightarrow$ add and subtract working left to right
=$-11-5$
=$-16$

Published by
Pearson

ISBN 10:
0321955048

ISBN 13:
978-0-32195-504-3

-16

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.